Pro-Inflammatory Profile of Children Exposed to Maternal Chikungunya Virus Infection during the Intrauterine Period: A One-Year Follow-Up Study - Renan Faustino; Fabiana Rabe Carvalho; Thalia Medeiros; Débora Familiar-Macedo; Renata Artimos de Oliveira Vianna; Paulo Emílio Côrrea Leite; Isabela Resende Pereira; Claudete Aparecida Araújo Cardoso; Elzinandes Leal De Azeredo; Andrea Alice Silva (Viruses, 2022)
Chikungunya virus (CHIKV) vertical transmission occurs due to maternal viremia in the prepartum. Clinical presentation in neonates can be varied; however, the consequences of intrauterine exposure on the immune response are unclear. Thus, we aimed to analyze inflammatory alterations in children exposed to maternal CHIKV infection. This is a cross-sectional study that included children exposed to maternal CHIKV infection (confirmed by RT-qPCR and/or IgM). Circulant immune mediators were analyzed by a multiplex assay. RESULTS: We included 33 children, with a mean age of 3 ± 2.9 months-old, and 19 (57.6%) were male. Only one child presented neurological alterations. CHIKV-exposed infants showed elevated levels of MIP-1α, MIP-1β, and CCL-2 (p < 0.05). Pro-inflammatory cytokines such as TNFα, IL-6, and IL-7 (p < 0.0001) were also increased. In addition, lower levels of PDGF-BB and GM-CSF were observed in the same group (p < 0.0001). Principal component (PC) analysis highlighted a distinction in the inflammatory profile between groups, where PC explained 56.6% of the alterations. Our findings suggest that maternal exposure to CHIKV can affect the circulating levels of pro-inflammatory cytokines during the infants’ first year of life. The long-term clinical consequences of these findings should be investigated.